2007
DOI: 10.1007/s11481-007-9072-4
|View full text |Cite
|
Sign up to set email alerts
|

Voltage-gated Potassium Channel Modulation of Neurotoxic Activity in Human Immunodeficiency Virus Type-1(HIV-1)-Infected Macrophages

Abstract: Macrophages play an important role in brain immune and inflammatory responses. They are also critical cells in mediating the pathology of neurodegenerative disorders such as HIV-associated dementia. This is largely through their capacity to secrete a variety of bioactive molecules such as cytokines, leading to neuronal dysfunction and/or death. Accumulating evidence indicates that voltage-gated potassium (Kv) channels play a pivotal role in the modulation of macrophage proliferation, activation, and secretion.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
6
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 48 publications
1
6
0
Order By: Relevance
“…In the present study, we have demonstrated that MCP-1, a glial-derived cytokine, enhanced outward K + currents and macrophage transmigration via regulation of Kv channel expression and channel activity. Our results herein fully support works by others demonstrating the expression of Kv channels in monocytes and macrophages (Mackenzie et al, 2003; Vicente et al, 2005; Vicente et al, 2006; Irvine et al, 2007; Villalonga et al, 2007). Voltage-gated K + channels including Kv1.3 channels are operative in blood-borne macrophages, tissue macrophages, and microglia, and are prominently induced concomitant with M-CSF-dependent proliferation.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…In the present study, we have demonstrated that MCP-1, a glial-derived cytokine, enhanced outward K + currents and macrophage transmigration via regulation of Kv channel expression and channel activity. Our results herein fully support works by others demonstrating the expression of Kv channels in monocytes and macrophages (Mackenzie et al, 2003; Vicente et al, 2005; Vicente et al, 2006; Irvine et al, 2007; Villalonga et al, 2007). Voltage-gated K + channels including Kv1.3 channels are operative in blood-borne macrophages, tissue macrophages, and microglia, and are prominently induced concomitant with M-CSF-dependent proliferation.…”
Section: Discussionsupporting
confidence: 92%
“…It is well known that differential channel regulation affects intracellular signals and is linked to macrophage activation and differentiation as well as to immune, morphological, and migratory responses of the cells (DeCoursey et al, 1996; Mackenzie et al, 2003; Fordyce et al, 2005; Rus et al, 2005; Vicente et al, 2005; Irvine et al, 2007). LPS-activation, for example, differentially regulates channel expression, as demonstrated by the induction of Kv1.3 channels and down-regulation of Kir2.1 channels.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently some experiments [14][15][16][17][18] found that activation of macrophages involved the change of membrane K + current which was closely associated with such cell functions as secretion of cytokines. The voltage-dependent K + channel in macrophages was intensively studied [19][20][21][22][23] . Silica particles, however, were not covered by those studies.…”
mentioning
confidence: 99%
“…Sheng-Di Chen's group reviewed the importance of CD200-CD200R interaction for microglia activation and its role in the pathogenesis of PD (Wang 2007). Huangui Xiong's laboratory summarized recent advances made in voltage-gated potassium channel for the regulation of macrophage-mediated neurotoxicity in HAD (Irvine et al 2007). Although the etiology of both diseases are different, it is now commonly accepted that microglia activation plays a pivotal role in the pathogenesis of many neurodegenerative disorders, including HAD, AD, and PD.…”
mentioning
confidence: 99%